A Paradigm Shift From Tradition To Modernity In Nollywoodas Projection Of African Narratives (Global Journal of Human-Social Science, 2026)
The Nollywood movie industry, since its inception in the early nineties, has progressively projected the African cultural heritage to other parts of the world. This encompasses both good and bad aspects of the culture. Today, many Africans in Diaspora tend to feel at home whenever they watch any of the Nollywood movies just like the Hollywood and Bollywood project, the American and Indian weltanshuung respectively. Interestingly, there has been a consistent transformation of the Hollywood and Bollywood from the traditional to the postmodern stages. This is not applicable to the Nollywood Industry. The paper, therefore argues that there should be a paradigmatic shift of Nollywood movies from tradition to modernity since virtually all the African Narratives being projected by the industry hitherto are not only pristine and anarchronistic but also fall short of the existing realities of the African way of life. This has impacted negatively on the socio-cultural development of Africa, and in particular portray some Nigerian ethnic groups as uncivilized and backward.
Keywords: Nollywood; Tradition; Modenity; Development